Акароидеи из гнезд рыжей полевки - Щур, Л.Е.; Головач, Г.П. (Вестник зоологии, 1982)
The Acaroid mite association in the nest of Clethrionomys glareolus S h r e b . is established to consist of seven species, their variety and abundance depend on the period of animal's residence within the nest, and is always higher than in forest litter.